1999
DOI: 10.1103/physrevlett.83.3214
|View full text |Cite
|
Sign up to set email alerts
|

Inherent Structure Entropy of Supercooled Liquids

Abstract: We present a quantitative description of the thermodynamics in a supercooled binary Lennard Jones liquid via the evaluation of the degeneracy of the inherent structures, i.e. of the number of potential energy basins in configuration space. We find that for supercooled states, the contribution of the inherent structures to the free energy of the liquid almost completely decouples from the vibrational contribution. An important byproduct of the presented analysis is the determination of the Kauzmann temperature … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
542
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 441 publications
(583 citation statements)
references
References 40 publications
39
542
2
Order By: Relevance
“…Since this relation is proposed to be valid in the limit of low T , it is a useful relation for studying the properties of a deeply supercooled liquid. Notably, several recent works showed that this prediction is obeyed at low T for binary LennardJones liquids [47,48,49]. This observation provided a physical basis for extrapolating U (and thermodynamic properties derived from it) to T near T g , and so made possible determination of the Kauzmann temperature for this system.…”
Section: Introductionmentioning
confidence: 96%
“…Since this relation is proposed to be valid in the limit of low T , it is a useful relation for studying the properties of a deeply supercooled liquid. Notably, several recent works showed that this prediction is obeyed at low T for binary LennardJones liquids [47,48,49]. This observation provided a physical basis for extrapolating U (and thermodynamic properties derived from it) to T near T g , and so made possible determination of the Kauzmann temperature for this system.…”
Section: Introductionmentioning
confidence: 96%
“…43,44 For solids and certain fluid states, the system can be assumed to spend the majority of its time in one of the local minima, only occasionally making excursions over the saddles separating the minima. Based on these ideas, as applied in previous work on supercooled liquids and glasses, 45,46 a direct computational approach for measuring the total ͑classical͒ free energy of a defect cluster has been developed; a brief discussion of the method is provided here and further details are given in Ref. 38.…”
Section: Computational Framework For Single Cluster Thermodynamicmentioning
confidence: 99%
“…Qualitatively, one may say that TLS probe the PEL on a very local scale whereas for the understanding of the glass transition much larger regions of the PEL are relevant. Here we would like to mention that in recent years computer simulations succeeded in extracting many important features of the PEL of supercooled liquids [26,27,28,29,30,31,32,33,34].…”
Section: Introductionmentioning
confidence: 99%